Method for producing composite for secondary battery electrode
The mechanochemical mixing of electrode active material with a fibrous carbon dispersion using a specific copolymer addresses the issues of high energy consumption and non-uniformity in composite production, leading to improved conductivity and performance in secondary battery electrodes.
Patent Information
- Application Number
- JP2023108281
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing methods for producing composite particles for secondary battery electrodes require high drying energy to remove solvents and struggle with uniform distribution of fibrous carbon, leading to non-uniform conductive networks and increased energy consumption.
A method involving mechanochemical mixing of electrode active material with a fibrous carbon dispersion using a copolymer containing specific structural units, followed by solvent removal and drying, to achieve uniform fibrous carbon adsorption on the active material surface.
This approach reduces drying energy consumption, enhances conductivity, and produces a homogeneous composite with high cohesive strength, resulting in high-output and long-life nonaqueous electrolyte secondary batteries.
Smart Images

Figure 2025007100000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a composite for a secondary battery electrode. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0003] Furthermore, as the applications of lithium-ion secondary batteries expand, there is a demand not only for improved battery performance, such as higher capacity, faster charging, and longer life, but also for reduced battery costs and a reduced environmental impact in production. In particular, there is a growing need to reduce the environmental impact, which in turn leads to reduced CO2 emissions, and the reduction of energy consumption in the production of lithium-ion secondary batteries, which account for a large portion of the costs and energy consumed in the production of electric vehicles, has become an issue.
[0004] To address the above issues, a method of manufacturing electrodes by powder molding that does not require a composite slurry has been proposed, since a large amount of drying energy is required to remove the solvent in conventional electrode manufacturing methods that use a composite slurry. In electrode manufacturing by powder molding, issues include improving productivity and making the electrode material uniform, so composite particles of active materials are used, which are expected to improve the fluidity of the material and narrow the particle size distribution. For example, Patent Document 1 discloses a method for increasing thickness accuracy at low basis weight during powder molding by controlling the particle size distribution of composite particles produced by spraying and drying a slurry for composite particles containing an electrode active material, a water-soluble polymer, a binder resin, and a dispersion medium. Furthermore, Patent Document 2 discloses an example of producing composite particles with excellent particle strength by spray granulating a slurry containing a positive electrode active material, carbon black, and cellulose nanofibers. In addition, composite particles of active materials are expected to be used not only in powder molding, but also in conventional manufacturing processes using composite slurries. In order to increase the capacity of secondary batteries, it is essential to increase the active material ratio in the electrode, so it is necessary to reduce the amount of auxiliary components. For this reason, the use of fibrous carbon, which has a small outer diameter and long fiber length and can form a conductive network with a small amount of addition, is seen as a promising conductive agent. However, it is difficult to distribute it uniformly in the electrode because it conflicts with the large cohesive force. Therefore, a method has been proposed that uses composite particles with fibrous carbon adsorbed on the surface of the active material in advance. For example, Patent Document 3 discloses an example in which positive electrode active material particles and fibrous carbon are dispersed in a solvent using an ultrasonic disperser, and the resulting slurry is spray-granulated to produce composite particles in which the materials are uniformly mixed, and the composite particles are then made into an electrode after preparing a composite slurry. Furthermore, Patent Document 4 discloses an example in which a positive electrode active material and carbon nanotubes are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6954424 [Patent Document 2] Patent No. 6380526 [Patent Document 3] Patent No. 5377946 [Patent Document 4] JP 2016-201228 A Summary of the Invention [Problem to be solved by the invention]
[0006] The methods disclosed in Patent Documents 1 to 3 require a spray granulation process when producing composite particles. A slurry in which the materials are uniformly dispersed is sprayed and instantly dried in a heating tank, making it possible to produce homogeneous composite particles. However, in order to spray the slurry in a spray form, it is necessary to reduce the viscosity of the slurry, and there is a limit to how much solid can be produced. Therefore, a larger amount of solvent is required than that used in conventional composite slurries, and the effect of reducing energy consumption in electrode production is not significant. In the method disclosed in Patent Document 4, composite particles can be produced without using a solvent because the carbon nanotubes are mixed in a powder state. However, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in non-uniform composite particles, making it difficult to form a uniform conductive network in the electrode.
[0007] The present invention aims to provide composite particles that can solve the above-mentioned problems, i.e., reduce the drying energy required to remove the solvent during electrode production, while also achieving a uniform composite of highly cohesive fibrous carbon and active material, and to provide a composite for secondary battery electrodes that can achieve high conductivity even in the electrode. [Means for solving the problem]
[0008] The present invention relates to a method for producing a composite for a secondary battery electrode, comprising an electrode active material and fibrous carbon, the method comprising the steps of: combining the electrode active material with a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer; and removing the solvent and drying the composite.
[0009] The present invention relates to a fibrous carbon dispersion comprising fibrous carbon, a dispersant, and a solvent, The present invention relates to the above-mentioned method for producing a composite for a secondary battery electrode, wherein the dispersant comprises a copolymer containing an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit.
[0010] The present invention relates to a copolymer comprising: The copolymer contains an aliphatic hydrocarbon structural unit, a nitrile group-containing structural unit, and an alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit, the aliphatic hydrocarbon structural unit contains an alkylene structural unit, the content of the aliphatic hydrocarbon structural unit is 40% by mass or more and less than 85% by mass based on the mass of the copolymer, the content of the nitrile group-containing structural unit is 15% by mass or more and 50% by mass or less based on the mass of the copolymer, and the content of the alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit is 10% by mass or less based on the mass of the copolymer; the total content of the aliphatic hydrocarbon structural unit, the nitrile group-containing structural unit, and the alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit is 80 mass% or more based on the mass of the copolymer, The present invention relates to the above-mentioned method for producing a composite for a secondary battery electrode, wherein the weight average molecular weight of the copolymer is 5,000 or more and 400,000 or less.
[0011] The present invention relates to the method for producing the composite for a secondary battery electrode, wherein the copolymer further contains less than 1 mass % of a carboxyl group-containing structural unit based on the mass of the copolymer. Regarding.
[0012] The present invention relates to the method for producing the composite for a secondary battery electrode, wherein the fibrous carbon dispersion contains 1 mass % or more and 20 mass % or less of a base based on the mass of the copolymer.
[0013] The method for producing the composite for secondary battery electrodes, wherein the composite for secondary battery electrodes has an exothermic peak temperature of 520°C or less of the fibrous carbon obtained by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere.
[0014] The present invention also relates to a method for producing the composite for a secondary battery electrode, wherein the composite for a secondary battery electrode contains a binder resin.
[0015] The present invention also relates to a method for producing an electrode film, comprising producing an electrode composite for a secondary battery according to the above method, and forming an electrode film using the electrode composite for a secondary battery.
[0016] The present invention relates to a method for producing a secondary battery, comprising producing an electrode composite for a secondary battery according to the above method, and forming an electrode film using the electrode composite for a secondary battery. Effect of the Invention
[0017] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 shows infrared spectra of Copolymer 1, Dispersant 1, and Dispersant 3 obtained by infrared spectroscopy using total reflectance measurement. [Diagram 2] FIG. 2 shows quantitative 13C-NMR spectra of Dispersant 1 and Dispersant 3 obtained by a nuclear magnetic resonance apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.
[0020] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."
[0021] <Method of manufacturing a composite for secondary battery electrode> The method for producing an electrode composite for a secondary battery of the present invention is characterized by including a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the resulting mixture.
[0022] In the process for producing the composite for secondary battery electrode of the present invention, the inclusion of the following (1) to (3) is an important factor for producing a composite having good resistance characteristics. (1) Uses a dispersion of fibrous carbon (2) Controlling the state of the mixture of the electrode active material and the dispersed carbon fiber (3) Compounding in a mechanochemical mixer The reasons for this will be explained below. (1) In order to adsorb fibrous carbon to the surface of an active material in the form of disintegrated primary particles or bundle particles, it is necessary to disintegrate the fibrous carbon, which has strong cohesive power, to the above-mentioned state, and dispersion in a liquid phase state (slurry) is essential for this. However, if it is combined with an active material in a slurry state, it is not possible to reduce the energy required to dry the solvent involved in electrode production. Therefore, it is necessary to use a dispersion of fibrous carbon in which the primary particles or bundle particles of fibrous carbon are uniformly dispersed and stabilized in advance. (2) By forming a composite in a non-slurry state with a high solid content concentration, it is possible to reduce the total amount of energy required to dry the solvent compared to the conventional electrode manufacturing method using a composite slurry. In addition, since a non-slurry mixture does not have fluidity as a liquid, separation of components during drying and drying aggregation of fibrous carbon can be suppressed even if the composition contains less resin components than a typical composite slurry. It is preferable that the solid content concentration of the non-slurry mixture is 80 mass % or more. The form of the mixture changes as follows depending on the solvent content. From the highest solvent content, the form is slurry (has liquid fluidity), clay (no liquid fluidity, sticky), crumbly (no liquid fluidity, no stickiness), and powder (absolutely dry). In this invention, non-slurry refers to clay or crumbly. These changes in form have a large effect not only on the appearance, but also on the mixing state of the mixture. It is more preferable for the mixture form in the composite of the present invention to be a crumbly mixture, as this can suppress drying and agglomeration of the fibrous carbon during the solvent removal process. (3) By mixing in a non-slurry state, it is expected that drying aggregation can be suppressed, but since it cannot flow as a liquid, the dispersion of fibrous carbon is difficult to wet and spread on the active material surface, and it is likely to become uneven. Therefore, by using a mechanochemical mixer capable of applying shear force to press the dispersion of fibrous carbon against the active material surface and promote wetting and spreading, it is expected that the fibrous carbon can be evenly adsorbed onto the active material surface while loosening the fibrous carbon. The above (1) to (3) make it possible to reduce the amount of drying energy required to prepare an electrode, to allow the fibrous carbon to be evenly adsorbed onto the surface of the active material in a loosened state, and to prevent separation of the components and aggregation of the fibrous carbon during drying during the process of concentrating and evaporating the solvent, thereby making it possible to obtain a composite and electrode with high electrical conductivity.
[0023] <Combining process using mechanochemical mixer> The mechanochemical mixer is not particularly limited as long as it is a device capable of mixing a non-slurry mixture by applying a shear force. Examples of such machines include high-speed mixers such as the Henschel Mixer and Super Mixer, particle compounding devices "Nanocure", "Nobilta", and "Mechanofusion" manufactured by Hosokawa Micron Corporation, powder surface modification device "Miraro" manufactured by Nara Machinery Works, "Hivismix" and "Hivisdepermix" manufactured by Primix, mixers "Planetary Mixer" and "Trimix" manufactured by Inoue Manufacturing Co., Ltd., and mixer / granulator "High Speed Mixer" manufactured by EarthTechnica Corporation. Among the mechanochemical mixers, planetary mixers, trimixes, and mechanofusions are preferred because they are capable of shear compounding and uniform mixing of materials.
[0024] <Electrode active material> The electrode active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. As the positive electrode active material, for example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxide (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li x Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g. Li x Mn 2-y Ni y O4), lithium phosphate powder with an olivine structure (e.g. Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g. V2O5, V6O 13) Examples include transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron(III) sulfate (Fe2(SO4)3), TiS2, and FeS. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These positive electrode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to have high basicity due to elution of components derived from raw materials or metal ions, and gelation of the binder resin and deterioration of the dispersion state are likely to occur due to this effect. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.
[0025] As the negative electrode active material, for example, metallic Li capable of reversibly doping or intercalating lithium ions, or an alloy thereof, a tin alloy, a silicon-based material (such as metallic Si, Si alloy, SiOx), a metal oxide-based material such as LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2, a conductive polymer such as polyacetylene or poly-p-phenylene, artificial graphite such as highly graphitized carbon material, or a carbonaceous powder such as natural graphite, or a resin-fired carbon material can be used. However, x is a number, where 0 < x < 1. These negative electrode active materials can also be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with an artificial graphite such as a highly graphitized carbon material, a carbonaceous powder such as natural graphite, or a resin-fired carbon material.
[0026] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, and has a high aspect ratio in the long axis direction, making it easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNTs are flat graphite rolled into a cylindrical shape, and include single-walled CNTs, double-walled CNTs, thin-walled (several-walled) CNTs, and multi-walled CNTs, and these may be mixed. Single-walled CNTs have a structure in which one layer of graphite is rolled. Multi-walled CNTs have a structure in which two or more layers of graphite are rolled. In addition, the sidewalls of CNTs do not have to have a graphite structure. In addition, for example, CNTs with sidewalls having an amorphous structure are also CNTs in this specification.
[0027] The shape of the CNT is not limited. Examples of such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet) and coil-like. Among them, the shape of the CNT is preferably needle-like or cylindrical tube-like. The CNT may be a single shape or a combination of two or more shapes.
[0028] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.
[0029] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it may be difficult to uniformly combine with the composite. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. Also, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.
[0030] <Dispersant> The dispersant for the fibrous carbon dispersion is preferably one that can disperse and stabilize the fibrous carbon in the fibrous carbon dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to the fibrous carbon and can provide good dispersion stability. Depending on the characteristics required for dispersing the fibrous carbon, a suitable type of dispersant can be used in a suitable amount.
[0031] Examples of the resin-type dispersant that can be used include (meth)acrylic polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose derivatives, and copolymers thereof. Examples of the polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, and nitrile rubbers. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, and amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, and polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with acetal (acetoacetal-modified or butyral-modified, etc.) by aldehydes. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, JP 2019-087304 A, Japanese Patent No. 6524479 A, and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymer of polyacrylonitrile, copolymer of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. Polymers in which other substituents have been introduced into a part of these polymers, modified polymers, etc. may also be used. The weight average molecular weight of the resin-type dispersant is preferably 500,000 or less, more preferably 300,000 or less, and more preferably 3,000 or more, and more preferably 5,000 or more, from the viewpoint of the balance of affinity between the dispersed substance and the dispersion medium and the resistance to the electrolyte. The resin-type dispersant may be used alone or in combination of two or more.
[0032] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, and Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Commercially available polyvinylpyrrolidone resins include, specifically, polyvinylpyrrolidone K30, K90 (manufactured by Fujifilm Wako), and K120 (manufactured by DSP Gokei Food & Chemical). Commercially available nitrile rubbers are available in various grades with different nitrile ratios, hydrogenation rates, and molecular weights under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and NipoleNBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used. Surfactants may be used in place of or in addition to the above-mentioned resin-type dispersants. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.
[0033] As the resin-type dispersant, a polymer containing at least an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit may be used. The aliphatic hydrocarbon structural unit of the polymer may contain an alkylene structural unit. The polymer may be hydrogenated.
[0034] As the dispersant, it is preferable to use one containing a copolymer containing an aliphatic hydrocarbon structural unit, a nitrile group-containing unit, and a carbamoyl group-containing structural unit as described below, since this can suppress aggregation of the fibrous carbon during drying of the composite. The aliphatic hydrocarbon structural unit contains at least an alkylene structural unit. The content of the aliphatic hydrocarbon structural unit is 40% by mass or more and less than 85% by mass based on the mass of the copolymer, the content of the nitrile group-containing unit is 15% by mass or more and 50% by mass or less based on the mass of the copolymer, and the content of the carbamoyl group-containing structural unit is 10% by mass or less based on the mass of the copolymer. It is more preferable that the weight average molecular weight of the copolymer is 5,000 or more and 400,000 or less, since this effectively suppresses the cohesive force of the fibrous carbon and leads to the production of a homogeneous composite.
[0035] In this specification, the copolymer may be referred to as "copolymer I." In addition, in this specification, a "substituted or unsubstituted carbamoyl group" (-CO-NR'2 (each R' is independently a hydrogen atom or a substituent)) may be referred to as an "amide group."
[0036] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.
[0037] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, an alkanetetrayl structural unit, etc. The aliphatic hydrocarbon structural unit contains at least an alkylene structural unit.
[0038] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.
[0039] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1A).
[0040] General formula (1A) [ka]
[0041] In general formula (1A), n represents an integer of 1 or more. n is preferably an integer of 2 or more, more preferably an integer of 3 or more, and particularly preferably an integer of 4 or more. n is preferably an integer of 6 or less, and more preferably an integer of 5 or less. In particular, n is preferably 4. In this specification, "*" represents a bond to another structure.
[0042] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1B).
[0043] General formula (1B) [ka]
[0044] In general formula (1B), n represents an integer of 1 or more. n is preferably an integer of 2 or more, and more preferably an integer of 3 or more. n is preferably an integer of 5 or less, and more preferably an integer of 4 or less. In particular, n is preferably 3.
[0045] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1C).
[0046] General formula (1C) [ka]
[0047] In general formula (1C), n represents an integer of 1 or more. n is preferably an integer of 4 or less, more preferably an integer of 3 or less, and even more preferably an integer of 2 or less. In particular, n is preferably 2.
[0048] The method for introducing an alkylene structural unit into Copolymer I is not particularly limited, and examples thereof include the following method (1a) or (1b).
[0049] In the method (1a), a copolymer is prepared by polymerization reaction using a monomer composition containing a conjugated diene monomer. The prepared copolymer contains a monomer unit derived from the conjugated diene monomer. In the present invention, the "monomer unit derived from the conjugated diene monomer" may be referred to as the "conjugated diene monomer unit", and the monomer unit derived from other monomers may be omitted in the same manner. Next, the conjugated diene monomer unit is hydrogenated to convert at least a part of the conjugated diene monomer unit into an alkylene structural unit. Hereinafter, "hydrogenation" may be referred to as "hydrogenation". The finally obtained copolymer I contains the unit obtained by hydrogenating the conjugated diene monomer unit as an alkylene structural unit.
[0050] The conjugated diene monomer unit includes at least a monomer unit having one carbon-carbon double bond. For example, the 1,3-butadiene monomer unit, which is a conjugated diene monomer unit, includes at least one monomer unit selected from the group consisting of a monomer unit having a cis-1,4 structure, a monomer unit having a trans-1,4 structure, and a monomer unit having a 1,2 structure, and may include two or more monomer units. The conjugated diene monomer unit may further include a monomer unit having no carbon-carbon double bond and including a branch point. In this specification, the "branch point" refers to a branch point in a branched polymer, and when the conjugated diene monomer unit includes a monomer unit having a branch point, the above prepared copolymer and copolymer I are branched polymers.
[0051] In the method (1b), a copolymer is prepared by polymerization reaction using a monomer composition containing an α-olefin monomer. The prepared copolymer contains α-olefin monomer units. The finally obtained copolymer I contains α-olefin monomer units as alkylene structural units.
[0052] Among these, the method (1a) is preferred because the copolymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene structural unit preferably contains a structural unit (hydrogenated conjugated diene monomer unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably contains a structural unit (hydrogenated 1,3-butadiene monomer unit) obtained by hydrogenating a 1,3-butadiene monomer unit. The conjugated diene monomer can be used alone or in combination of two or more kinds.
[0053] The hydrogenation is preferably a method capable of selectively hydrogenating conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.
[0054] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a copolymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include nickel, palladium, platinum, copper, etc.
[0055] In the method (1b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.
[0056] The alkylene structural unit preferably includes at least one selected from the group consisting of structural units containing a linear alkylene structure and structural units containing a branched alkylene structure, more preferably includes at least one selected from the group consisting of structural units consisting only of linear alkylene structures and structural units consisting only of branched alkylene structures, and further preferably includes at least one selected from the group consisting of structural units represented by the above formula (1B) and structural units represented by the above formula (1C).
[0057] The alkylene structural unit may include a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure. When the alkylene structural unit includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is preferably 70% by mass or less, more preferably 65% by mass or less, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100% by mass). In particular, it is preferably 20% by mass or less, more preferably 18% by mass or less, and even more preferably 15% by mass or less. When the copolymer I includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is, for example, 1% by mass or more, may be 5% by mass or more, or may be 10% by mass or more, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100% by mass).
[0058] In the aliphatic hydrocarbon structural unit, the content of the alkylene structural unit is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass). The content of the alkylene structural unit is, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass), for example, less than 100% by mass, and may be 99.5% by mass or less, 99% by mass or less, or 98% by mass or less. The content of the alkylene structural unit may be 100% by mass.
[0059] The content of the aliphatic hydrocarbon structural unit is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the mass of copolymer I (i.e., when the mass of copolymer I is 100% by mass). The content of the aliphatic hydrocarbon structural unit is preferably less than 85% by mass, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on the mass of copolymer I (i.e., when the mass of copolymer I is 100% by mass).
[0060] The nitrile group-containing structural unit is a structural unit containing a nitrile group, preferably a structural unit containing an alkylene structure substituted with a nitrile group, more preferably a structural unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one.
[0061] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (2A).
[0062] General formula (2A) [ka]
[0063] In formula (2A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.
[0064] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (2B).
[0065] General formula (2B) [ka]
[0066] In formula (2B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.
[0067] The method of introducing the nitrile group-containing structural unit into the copolymer I is not particularly limited, but a method of preparing a copolymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer (method (2a)) can be preferably used. The finally obtained copolymer I contains a nitrile group-containing monomer unit as a nitrile group-containing structural unit. Examples of the nitrile group-containing monomer capable of forming the nitrile group-containing structural unit include a monomer containing a polymerizable carbon-carbon double bond and a nitrile group. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the intermolecular force between the copolymers I and / or between the copolymer I and the dispersed substance (adsorbed substance), it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.
[0068] The content of the nitrile group-containing structural unit is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). The content of the nitrile group-containing structural unit is preferably 50% by mass or less, more preferably 46% by mass or less, and even more preferably 40% by mass or less, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). By setting the content of the nitrile group-containing structural unit within the above range, the adsorption to the dispersed material and the affinity to the dispersion medium can be controlled, and the dispersed material can be stably present in the dispersion medium. In addition, the affinity of the copolymer I to the electrolyte can be controlled, and problems such as the copolymer I dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented.
[0069] The amide group-containing structural unit is a structural unit containing an amide group, preferably a structural unit containing an alkylene structure substituted with an amide group, more preferably a structural unit consisting of only an alkylene structure substituted with an amide group. The alkylene structure is preferably a linear or branched alkylene structure. The amide group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with an amide group. The number of amide groups contained in the amide group-containing structural unit is preferably one. The amide group is a substituted or unsubstituted carbamoyl group, and examples of the substituent include an alkyl group and a hydroxyalkyl group. By including an amide group-containing structural unit in the copolymer I, the adsorption force to the dispersed material can be significantly improved, and the dispersibility and robustness can be improved. In addition, since the amide group can form a strong hydrogen bond, a crosslinked structure due to hydrogen bonds may be introduced into the molecule of the copolymer I by including an amide group-containing structural unit in the copolymer I. The copolymer I to which the crosslinked structure has been introduced can be three-dimensionally adsorbed to the dispersed material, so that the dispersibility and robustness can be further improved.
[0070] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3A).
[0071] General formula (3A) [ka]
[0072] In the general formula (3A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2. Each R' independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. It is preferable that at least one R' is a hydrogen atom, and more preferably two R' are hydrogen atoms.
[0073] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3B).
[0074] General formula (3B) [ka]
[0075] In the general formula (3B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom. Each R' independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. At least one R' is preferably a hydrogen atom, and more preferably two R's are hydrogen atoms.
[0076] The method for introducing an amide group-containing structural unit into Copolymer I is not particularly limited, and examples thereof include the following method (3a) or (3b).
[0077] In the method (3a), a copolymer is prepared by polymerization reaction using a monomer composition containing an amide group-containing monomer. The prepared copolymer contains amide group-containing monomer units. The finally obtained copolymer I contains the amide group-containing monomer units as amide group-containing structural units.
[0078] In the method (3b), a copolymer containing a nitrile group-containing structural unit is prepared. Then, the nitrile group contained in the nitrile group-containing structural unit is hydrolyzed under a basic atmosphere to convert at least a part of the nitrile group-containing structural unit into an amide group-containing structural unit. The copolymer containing the nitrile group-containing structural unit can be obtained, for example, by the above method (2a). The finally obtained copolymer I contains, as an amide group-containing structural unit, a unit obtained by modifying the nitrile group contained in the nitrile group-containing structural unit by hydrolysis.
[0079] When the copolymer I is prepared via the method (3b), the introduction of amide groups into the copolymer I can be confirmed by NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements. In addition, it can be confirmed simply by the change in weight average molecular weight and / or viscosity (solution viscosity) between the copolymer before hydrolysis and the copolymer I. The weight average molecular weight of the copolymer I tends to be smaller than the weight average molecular weight of the copolymer before hydrolysis (for example, 0.05 to 0.6 times). In addition, for example, the viscosity of the solution of the copolymer I at a shear stress of 1,000 / s tends to be smaller than the viscosity of the solution of the copolymer before hydrolysis at a shear stress of 1,000 / s (for example, 0.05 to 0.6 times). It should be noted that, regardless of the preparation method of the copolymer I, the introduction of amide groups into the copolymer I can be confirmed by NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements.
[0080] In the method (3a), examples of the amide group-containing monomer include monoalkyl (meth)acrylamides such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-isopropyl (meth)acrylamide; dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; N-(hydroxyalkyl) (meth)acrylamides such as N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, and N-(2-hydroxybutyl) (meth)acrylamide; diacetone (meth)acrylamide; and acryloylmorpholine. In this specification, "(meth)acryl" refers to acryl or methacryl. In particular, the amide group-containing monomer preferably includes at least one selected from the group consisting of acrylamide, methacrylamide, and N,N-dimethylacrylamide. The amide group-containing monomers can be used alone or in combination of two or more.
[0081] In the method (3b), in order to create a basic atmosphere, at least one base selected from the group consisting of inorganic bases and organic hydroxides (organic bases) can be used.
[0082] Examples of inorganic bases include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, or borates of alkali metals or alkaline earth metals; and ammonium hydroxide. Among these, hydroxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.
[0083] The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, cetyl trimethyl ammonium hydroxide, hexadecyl trimethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, it is particularly preferable to use at least one selected from the group consisting of trimethyl-2-hydroxyethyl ammonium hydroxide and tetramethyl ammonium hydroxide.
[0084] The amount of the base used is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the mass of the copolymer. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the copolymer. If the amount used is too small, the denaturation of the nitrile group by hydrolysis tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0085] In the method (3b), hydrolysis can be carried out by mixing a copolymer containing an alkylene structural unit and a nitrile group-containing monomer unit, a base, and a solvent. Any other components may be mixed. There is no limitation on the order of addition of the copolymer, the base, and the solvent to the container and the mixing method, and they may be added to the container at the same time; the copolymer, the base, and the solvent may be added separately to the container; or one or both of the copolymer and the base may be mixed with the solvent to prepare a copolymer-containing liquid and / or a base-containing liquid, and the copolymer-containing liquid and / or the base-containing liquid may be added to the container. In particular, since the nitrile group can be efficiently modified, a method in which a base dispersion in which a base is dispersed in a solvent is added to a copolymer solution in which the copolymer is dissolved in a solvent while stirring is preferred. A disperser (dispersing machine) or a homogenizer can be used for stirring. As the solvent, the solvents listed in the description of the dispersant composition described later can be used.
[0086] There is no limit to the temperature during mixing, but the denaturation can be accelerated by heating to 30°C or higher. In addition, a small amount of water and / or alcohol may be added to the container to promote the denaturation. Water and / or alcohol may be added to the container while mixing the copolymer and the base, or before adding the copolymer and the base to the container, or may be added to the container simultaneously with or subsequent to the copolymer and the base. In addition, when the copolymer, the base, and any optional components used as necessary are highly hygroscopic, water may be contained as absorbed water. The amount of water and / or alcohol is preferably 0.05 to 20% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.05 to 1% by mass, based on the mass of the copolymer.
[0087] Examples of alcohols include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, and thiodiglycol. The alcohols can be used alone or in combination of two or more. The hydrolysis is preferably carried out in the presence of at least one selected from the group consisting of methanol, ethanol, and water, and is particularly preferably carried out in the presence of water.
[0088] The content of the amide group-containing structural unit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 1% by mass or less, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). When the content of the amide group-containing structural unit is below the above range, the hydrogen bonds between the copolymers I become too strong, which may cause the fibrous carbon dispersion to gel during storage, can be prevented. The content of the amide group-containing structural unit is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and particularly preferably 0.7% by mass or more, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). When the content of the amide group-containing structural unit is above the above range, the adsorption force to the dispersed material can be sufficiently improved, and a good effect of improving dispersibility and robustness can be obtained.
[0089] Copolymer I may contain any structural unit. Examples of the structural unit include a carboxyl group-containing structural unit, an alkenylene structural unit, an alkyl structural unit, and a structural unit containing a branch point such as an alkanetriyl structural unit or an alkanetetrayl structural unit. The structural unit containing a branch point is a structural unit different from the structural unit containing a branched alkylene structure and the structural unit containing a branched alkyl structure.
[0090] The carboxyl group-containing structural unit is a structural unit containing a carboxyl group, preferably a structural unit containing an alkylene structure substituted with a carboxyl group, more preferably a structural unit consisting of only an alkylene structure substituted with a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The carboxyl group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a carboxyl group. The number of carboxyl groups contained in the carboxyl group-containing structural unit is preferably one or two. By including a carboxyl group-containing structural unit in the copolymer I, the adsorption force to the dispersed material can be significantly improved, and the viscosity of the fibrous carbon dispersion can be reduced, thereby improving the dispersion efficiency.
[0091] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4A).
[0092] General formula (4A) [ka]
[0093] In formula (4A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.
[0094] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4B).
[0095] General formula (4B) [ka]
[0096] In formula (4B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.
[0097] The method for introducing the carboxyl group-containing structural unit is not particularly limited, but examples thereof include the following method (4a) or (4b).
[0098] In the method (4a), a copolymer is prepared by polymerization reaction using a composition containing a carboxyl group-containing monomer. The prepared copolymer contains a carboxyl group-containing monomer unit. The finally obtained copolymer I contains the carboxyl group-containing monomer unit as a carboxyl group-containing structural unit.
[0099] In the method (4b), a copolymer containing an amide group-containing structural unit is prepared. Then, the amide group contained in the amide group-containing structural unit is hydrolyzed under an acidic atmosphere to convert the amide group-containing structural unit into a carboxyl group-containing structural unit. The copolymer containing an amide group-containing structural unit can be obtained, for example, by the above method (3a) or (3b). The finally obtained copolymer I contains, as a carboxyl group-containing structural unit, a unit obtained by modifying the amide group contained in the amide group-containing structural unit by hydrolysis.
[0100] In the method (4a), examples of the carboxyl group-containing monomer include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and isocrotonic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, glutaconic acid, and itaconic acid. In particular, the carboxyl group-containing monomer preferably contains at least one selected from the group consisting of acrylic acid and maleic acid. The carboxyl group-containing monomer may be used alone or in combination of two or more.
[0101] In the method (4b), in order to create an acidic atmosphere, at least one acid selected from the group consisting of inorganic acids and organic acids can be used.
[0102] Examples of inorganic acids include hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, hydrofluoric acid, etc. Examples of organic acids include formic acid, acetic acid, citric acid, oxalic acid, succinic acid, malic acid, benzoic acid, benzenesulfonic acid, etc. Among these, succinic acid and citric acid are preferred.
[0103] The amount of the acid used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the mass of the copolymer. The amount of the acid used is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the mass of the copolymer. If the amount used is too small, the amide group tends not to denature due to hydrolysis. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0104] The content of the carboxyl group-containing structural unit is preferably less than 1% by mass, more preferably 0.5% by mass or less, and even more preferably 0.3% by mass or less, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). If the content of the carboxyl group-containing structural unit is less than (or less than) the above range, the hydrogen bonds between the copolymers I become too strong, which can cause the problem of the fibrous carbon dispersion gelling during storage, which will be described later, can be prevented. The content of the carboxyl group-containing structural unit is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.3% by mass or more, based on the mass of the copolymer I (i.e., when the mass of the copolymer I is 100% by mass). If the content of the carboxyl group-containing structural unit is more than the above range, the adsorption force to the dispersed material can be sufficiently improved, and the viscosity of the fibrous carbon dispersion can be reduced, thereby improving the dispersion efficiency.
[0105] The alkenylene structural unit is a structural unit containing an alkenylene structure, and is preferably a structural unit consisting of only an alkenylene structure. The alkenylene structure is preferably a linear alkenylene structure or a branched alkenylene structure.
[0106] The alkenylene structural unit preferably includes at least one selected from the group consisting of a structural unit containing a linear alkenylene structure and a structural unit containing a branched alkenylene structure, and more preferably includes at least one selected from the group consisting of a structural unit consisting only of a linear alkenylene structure and a structural unit consisting only of a branched alkenylene structure.
[0107] For example, when copolymer I is obtained through the above method (1a), a conjugated diene monomer unit having a carbon-carbon double bond within the unit may remain within the molecule without being hydrogenated in copolymer I. The finally obtained copolymer I may contain a conjugated diene monomer unit having a carbon-carbon double bond within the unit as an alkenylene structural unit.
[0108] The alkyl structural unit is a structural unit containing an alkyl structure (however, it is a structural unit that does not fall under other aliphatic hydrocarbon structural units such as branched alkylene structural units, nitrile group-containing structural units, amide group-containing structural units, and carboxyl group-containing structural units), and is preferably a structural unit consisting of only an alkyl structure. The alkyl structure is preferably a linear alkyl structure or a branched alkyl structure.
[0109] The alkyl structural unit preferably includes at least one type selected from the group consisting of structural units containing a linear alkyl structure and structural units containing a branched alkyl structure, and more preferably includes at least one type selected from the group consisting of structural units consisting only of a linear alkyl structure and structural units consisting only of a branched alkyl structure.
[0110] For example, when the copolymer I is obtained via the above method (1a) or (1b), it is preferable that at least a hydrogenated conjugated diene monomer unit or an α-olefin monomer unit is introduced into the copolymer I as a terminal group of the copolymer I. The finally obtained copolymer I may contain these monomer units as alkyl structural units.
[0111] The alkanetriyl structural unit is a structural unit containing an alkanetriyl structure, and is preferably a structural unit consisting of only an alkanetriyl structure. The alkanetetrayl structural unit is a structural unit containing an alkanetetrayl structure, and is preferably a structural unit consisting of only an alkanetetrayl structure.
[0112] For example, when the copolymer I is obtained through the above method (1a), the conjugated diene monomer unit may be introduced into the molecule of the copolymer I as a monomer unit having no carbon-carbon double bond and having a branch point. In this case, the finally obtained copolymer I is a branched polymer, and may contain the conjugated diene monomer unit as an aliphatic hydrocarbon structural unit having a branch point, such as an alkanetriyl structural unit or an alkanetetrayl structural unit. When the aliphatic hydrocarbon structural unit contains a structural unit having a branch point, the copolymer I is a branched polymer. The branched polymer may be a network polymer. The copolymer I containing a structural unit having a branch point can be three-dimensionally adsorbed to the dispersed material, and therefore can further improve dispersibility and robustness.
[0113] Preferred embodiments of the copolymer I include the following. The total content of the aliphatic hydrocarbon structural units, the nitrile group-containing structural units, and the carbamoyl group-containing structural units contained in the copolymer I is 80% by mass or more and 100% by mass or less based on the mass of the copolymer I. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. The total content of the aliphatic hydrocarbon structural units, the nitrile group-containing structural units, the carbamoyl group-containing structural units, and the carboxyl group-containing structural units contained in the copolymer I is 80% by mass or more and 100% by mass or less based on the mass of the copolymer I. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. A copolymer I comprising a structural unit represented by general formula (1A), a structural unit represented by general formula (2A), and a structural unit represented by general formula (3A), and may comprise a structural unit represented by general formula (4A) as an optional structural unit, the total content of the structural units being 80% by mass or more and 100% by mass or less based on the mass of the copolymer I. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. A copolymer I comprising a structural unit represented by general formula (1B), a structural unit represented by general formula (2B), and a structural unit represented by general formula (3B), and may comprise a structural unit represented by general formula (4B) as an optional structural unit, the total content of the structural units being 80% by mass or more and 100% by mass or less based on the mass of the copolymer I. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.
[0114] In this specification, the content of the structural unit can be determined by utilizing the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurement.
[0115] Preferred embodiments of the method for producing copolymer I include the following: A method for producing copolymer I, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer (methods (1a) and (2a)), hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)), and modifying the nitrile group-containing structural units contained in the copolymer by hydrolysis (method (3b)). In this method, a part or all of the conjugated diene monomer units are hydrogenated. Also, a part (but not all) of the nitrile group-containing structural units are modified by hydrolysis so that the copolymer I contains a nitrile group-containing structural unit. A method for producing copolymer I, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer, a nitrile group-containing monomer, and an amide group-containing monomer (methods (1a), (2a), and (3a)), and hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)). In this process, some or all of the conjugated diene monomer units are hydrogenated.
[0116] In the above-mentioned embodiment of the production method, the monomer composition may further contain a carboxyl group-containing monomer. Alternatively, the above-mentioned embodiment of the production method may further include modifying the amide group-containing structural unit by hydrolysis (method (4b)), in which a part (but not all) of the amide group-containing structural unit is modified by hydrolysis.
[0117] The copolymer I produced by the method of (3b) can be used as a dispersant in the state of a mixture (dispersant-containing liquid) containing the copolymer I, a base, and a solvent after hydrolysis. Alternatively, the copolymer I produced by the method of (3b) can be used as a dispersant in the state of a mixture (dispersant-containing liquid) containing the copolymer I and a solvent after extracting and removing the base from the mixture (dispersant-containing liquid) containing the copolymer I, a base, and a solvent after hydrolysis. The method of extracting and removing the base is not particularly limited, but for example, a method of dropping the mixture (dispersant-containing liquid) into a washing solvent that is a good solvent for the base and a poor solvent for the copolymer I, and recovering the precipitated copolymer I can be mentioned. The more the washing solvent, the higher the removal efficiency. In addition, the removal efficiency can be increased by redissolving the precipitated copolymer I and repeatedly washing the copolymer I. The solvent that is a good solvent for the base and a good solvent for the copolymer I may be thoroughly mixed with the mixture (dispersant-containing liquid) and then washed in the same manner.
[0118] The polymerization reaction used for preparing the copolymer is preferably an emulsion polymerization reaction, and a conventional emulsion polymerization method can be used. Polymerization agents such as emulsifiers (surfactants), polymerization initiators, chelating agents, oxygen scavengers, and molecular weight regulators used in emulsion polymerization can be any conventionally known agent, and are not particularly limited. For example, anionic emulsifiers or anionic and nonionic emulsifiers are usually used as emulsifiers.
[0119] Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include polyethylene glycol ester type, polypropylene glycol ester type, and block copolymer type emulsifiers of ethylene oxide and propylene oxide, etc.
[0120] Examples of the polymerization initiator include thermal decomposition initiators such as persulfates, such as potassium persulfate and ammonium persulfate; organic peroxides, such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; azo compounds, such as azobisisobutyronitrile; and redox initiators consisting of these and a reducing agent, such as divalent iron ions. Among these, redox initiators are preferred. The amount of the initiator used is, for example, in the range of 0.01 to 10% by mass with respect to the total amount of the monomers.
[0121] The emulsion polymerization reaction may be either a continuous or batch type. The polymerization temperature may be either low-temperature or high-temperature polymerization, but is preferably 0 to 50°C, more preferably 0 to 35°C. The method of adding the monomer (lump addition, divided addition, etc.), the polymerization time, the polymerization conversion rate, etc. are not particularly limited. The conversion rate is preferably 85% by mass or more, more preferably 90% by mass or more.
[0122] The weight average molecular weight of the copolymer I is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. The weight average molecular weight of the copolymer I is preferably 400,000 or less, more preferably 350,000 or less, and even more preferably 300,000 or less. When the weight average molecular weight of the copolymer I is 5,000 or more and 400,000 or less, the adsorption to the dispersed material and the affinity to the dispersion medium are good, and the stability of the dispersion tends to be improved. The weight average molecular weight is a weight average molecular weight in terms of polystyrene, and can be measured by gel permeation chromatography (GPC). Specifically, it may be measured by the method described in the examples.
[0123] The dispersant contains at least copolymer I. The dispersant may further contain any polymer, any copolymer, etc. The content of copolymer I in the dispersant is preferably 50% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more. The content of copolymer I in the dispersant may be 100% by mass, in which case the dispersant consists of only copolymer I.
[0124] <Dispersant Composition> The dispersant composition contains a dispersant, a base in an amount of 1% by mass or more and 20% by mass or less based on the mass of copolymer I, and a solvent. That is, the dispersant composition contains copolymer I, a base in an amount of 1% by mass or more and 20% by mass or less based on the mass of copolymer I, and a solvent. When copolymer I is obtained through the above-mentioned method (3b), the dispersant composition may contain the base used in the method (3b). The content of the base is 1% by mass or more, preferably 2% by mass or more, and more preferably 3% by mass or more, based on the mass of copolymer I. From the viewpoint of preventing gelation and thickening over time, and corrosion inside the dispersing device and / or the battery, the content of the base is 20% by mass or less, preferably 15% by mass or less, and more preferably 10% by mass or less, based on the mass of copolymer I. The dispersant composition may contain any component such as an acid.
[0125] The dispersant composition contains a solvent. The solvent is preferably a solvent capable of dissolving Copolymer I, and is preferably a solvent made of any one of water-soluble organic solvents or a mixed solvent made of two or more of water-soluble organic solvents.
[0126] Examples of the water-soluble organic solvent include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), and others such as tetrahydrofuran, urea, and acetonitrile. The water-soluble organic solvent preferably contains an amide organic solvent, and more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.
[0127] The content of copolymer I in the dispersant composition is preferably 2% by mass or more, more preferably 5% by mass or more, based on the mass of the dispersant composition, from the viewpoint of ensuring a sufficient concentration of the conductive material and / or electrode active material in the fibrous carbon dispersion, the binder resin-containing fibrous carbon dispersion, and the slurry for electrode membrane. When the concentration of the conductive material and / or electrode active material is sufficient, good coatability is obtained, and an increase in production cost due to an increase in drying time and transportation cost can be prevented. The content of copolymer I is preferably 15% by mass or less, more preferably 10% by mass or less, based on the mass of the dispersant composition, from the viewpoint of preventing the generation of insoluble matter.
[0128] The mixture (dispersant-containing liquid) containing copolymer I, a base, and a solvent obtained through the above-mentioned method (3b) may be used as a dispersant composition. Also, the mixture (dispersant-containing liquid) containing copolymer I, a base, an acid, and a solvent obtained through the above-mentioned methods (3b) and (4b) may be used as a dispersant composition.
[0129] <Solvent> The solvent (dispersion medium) of the fibrous carbon dispersion is not particularly limited, but is preferably a high dielectric constant solvent, and preferably contains one of the high dielectric constant solvents or a mixed solvent of two or more of them. In addition, the high dielectric constant solvent may be mixed with one or more other solvents.
[0130] Examples of high dielectric constant solvents that can be used include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), water, and others such as tetrahydrofuran, urea, and acetonitrile. The dispersion medium preferably contains an amide-based organic solvent or water, and the amide-based organic solvent more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent can be a value listed in the Solvent Handbook, etc., and is preferably 2.5 or more at 20°C.
[0131] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a solvent (dispersion medium), and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.
[0132] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.
[0133] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.
[0134] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.
[0135] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a non-aqueous solvent such as NMP, dropping the diluted fibrous carbon dispersion onto a substrate, drying the diluted fibrous carbon dispersion, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.
[0136] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass, and even more preferably 0.5 to 10% by mass. Also, it is preferable that the content of the fibrous carbon is appropriately adjusted so that a fibrous carbon dispersion having appropriate fluidity or viscosity is obtained, depending on the specific surface area of the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc.
[0137] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.
[0138] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.
[0139] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.
[0140] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.
[0141] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.
[0142] The specific surface area of fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and2 / g or less is more preferable. The specific surface area of the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.
[0143] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.
[0144] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.
[0145] When fibrous carbon is dispersed in a disperser by collision with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon may be broken and short-flaked carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.
[0146] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.
[0147] <Drying process> The method for removing the solvent and drying is not particularly limited as long as it can remove the solvent from the non-slurry mixture, and examples of the method include drying methods such as hot air drying, vacuum drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.
[0148] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material, fibrous carbon, and may further contain an optional binder resin. The composite for an electrode may further contain optional components.
[0149] The fibrous carbon contained in the electrode composite of the present invention is at least partially crushed and adheres to the surface of the active material.
[0150] The presence of fibrous carbon in a crushed form on the surface of the active material can efficiently supply electrons required for the battery reaction to the active material, and can also contribute to reducing the contact resistance between active materials when an electrode is fabricated. Therefore, when the fibrous carbon is crushed and uniformly adsorbed on the surface of the active material, and a certain number of aggregates of fibrous carbon are included, when the electrode is used for a secondary battery, the electrode resistance is reduced and the formation of an electronic conduction path to the active material during the battery reaction is favored, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.
[0151] The crushed form of fibrous carbon refers to a form in which secondary particles (aggregates) of fibrous carbon are broken down into primary particles or a bundle state in which multiple primary particles are bundled together. The state in which fibrous carbon is crushed and adsorbed onto the active material surface includes a state in which the primary particles and / or bundles are isolated, and a state in which the primary particles and / or bundles are overlapped. From the viewpoint of electron supply to the active material and conductive paths between composites, a state in which the primary particles and / or bundles are overlapped and adsorbed in a mesh-like shape is preferred.
[0152] In the present invention, the state in which the fibrous carbon is adsorbed on the surface of the active material in a crushed form means that the area of the fibrous carbon adsorbed on the active material in a crushed fiber state is 10% or more of the entire surface of the active material, preferably 20% or more, and more preferably 50% or more.
[0153] The area occupied by the fibrous carbon adsorbed to the active material in the crushed fiber state can be measured from the contrast difference between the active material and the fibrous carbon in images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average value of the above areas calculated from 20 pieces of active material in the composite was used.
[0154] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 520° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.
[0155] The exothermic peak temperature of the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the top of the maximum exothermic peak resulting from the combustion of the fibrous carbon, which is located in the vicinity of 300 to 700°C, is read and determined as the exothermic peak temperature of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.
[0156] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 520°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.
[0157] When the volume resistivity of the electrode composite for secondary batteries is 500 Ω·cm or less under a load of 20 kN, the fibrous carbon in the composite is not unevenly distributed and is adsorbed on the active material in a more uniform state, which reduces the electrode resistance when used as a secondary battery electrode. A volume resistivity of 100 Ω·cm or less is preferable, and 50 Ω·cm or less is more preferable.
[0158] The volume resistivity of the electrode composite for secondary batteries can be determined by performing resistivity measurement based on the four-terminal four-probe method. Specifically, four needle-like probes (electrodes) are brought into contact with the composite for secondary battery electrodes to be measured, and the resistance of the test piece is calculated from the current flowing between the two outer probes and the potential difference generated between the two inner probes. The volume resistivity of the CNTs can then be calculated from the measured resistance and the thickness of the test piece. The measurement is performed using a volume resistivity measuring device (for example, the low-resistance version of the automatic powder resistivity measuring system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd.) under a load of 20 kN.
[0159] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.
[0160] As mentioned above, when the combustion temperature is 520°C or less and the volume resistivity is 100 Ω·cm or less, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, which is preferable because when used as an electrode for a secondary battery, it reduces the electrode resistance and is favorable for the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, because an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.
[0161] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.
[0162] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.
[0163] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Particularly, fluororesins are preferred, such as polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and modified products thereof. These may be used alone or in combination of two or more. Among these, from the standpoint of resistance, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, resins having these structural units, and modified products thereof are preferred.
[0164] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.
[0165] <Electrode for secondary batteries> The secondary battery electrode of the present invention includes a composite for a secondary battery electrode. The electrode may further include optional components such as a binder and a dispersant. In general, the electrode is formed by powder compression molding or by applying a composite slurry onto a current collector and removing volatiles.
[0166] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.
[0167] <Method of manufacturing secondary battery electrodes> A secondary battery electrode can be formed by adding a binder or the like to a composite for a secondary battery electrode, forming each component into a sheet by pressing or the like under dry conditions that do not contain solvents, and then powder pressure molding the sheet, or by preparing a composite slurry, coating it on a current collector, and removing the volatile components. The powder pressure molding method without using a composite slurry is preferable because it can reduce the energy consumption required for drying the solvent.
[0168] The method for powder compression molding is not particularly limited, and any known method can be used. When an electrode is produced by powder pressure molding without using a composite material slurry, a dry mixture in which the electrode composite and a binder are mixed in advance, or a dried product after wet mixing may be used. The method for adding a binder or the like to the secondary battery electrode composite and dry-mixing or wet-mixing each component is not particularly limited, and various dispersing machines, mixers, granulators, etc. can be appropriately selected.
[0169] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode by powder pressure molding and forming each component into a sheet by pressing or the like, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed in advance on a current collector.
[0170] Examples of the method for powder pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.
[0171] The method for producing an electrode using the composite slurry is not particularly limited, and a known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after coating, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.
[0172] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0173] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.
[0174] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector, and the negative electrode may be an electrode film containing a negative electrode active material formed on a current collector.
[0175] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.
[0176] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0177] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.
[0178] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.
[0179] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.
[0180] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES
[0181] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In the examples, a "dispersant-containing liquid" containing a "dispersant" and a solvent may be referred to as a "dispersant solution".
[0182] <Preparation of sample for weight average molecular weight (Mw) measurement> The copolymer was separated and collected from the dispersant-containing liquid (dispersant composition) containing the copolymer, base, and solvent by the following method, and used as a measurement sample. The dispersant-containing liquid was dropped into purified water to precipitate the copolymer, and the precipitate was collected by filtering through a Buchner funnel. The precipitate was rinsed by sprinkling purified water on the Buchner funnel as it was, and then dissolved in tetrahydrofuran (THF) to obtain a solution. The obtained solution was dropped again into purified water to perform the filtration and washing steps using purified water, and the precipitate was redissolved in THF to obtain a measurement sample. In addition, the conductive material was separated from the fibrous carbon dispersion containing the copolymer, base, solvent, and conductive material by centrifugation, and the same steps as above were performed on the separated supernatant to prepare a measurement sample.
[0183] <Measurement of weight average molecular weight (Mw)> The weight average molecular weight (Mw) of the copolymer was measured by gel permeation chromatography (GPC) equipped with an RI detector. The apparatus used was HLC-8320GPC (manufactured by Tosoh Corporation), and three separation columns were connected in series. The packing materials were "TSK-GELSUPERAW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Corporation, respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The weight average molecular weight is a polystyrene equivalent value.
[0184] <Measurement of viscosity of copolymer solution and dispersant-containing solution> The copolymer was dissolved in NMP as a solvent to give an 8% solution, and the resulting solution was used as a viscosity measurement sample. The dispersant-containing liquid (dispersant composition) was diluted with NMP to give an 8% solution to give a viscosity measurement sample. The viscosity measurement sample was set on a sample stage, and the viscosity was continuously measured from shear stress 1 / s to 1,000 / s using a rheometer (RheoStress1 rotational rheometer manufactured by ThermoFisherScientific Co., Ltd.) at 25°C, a diameter of 60 mm, and a 2° cone.
[0185] <Infrared spectroscopic analysis using total reflectance measurement method> The solid copolymer was used as it was for the measurement. The dispersant-containing liquid (dispersant composition) was treated with hot air at 100°C for 10 hours to thoroughly dry and solidify the solid copolymer, which was used as the measurement sample. The measurement sample was subjected to IR measurement using an infrared spectrophotometer (Nicoleti S5 FT-IR spectrometer manufactured by Thermo Fisher Scientific Co., Ltd.).
[0186] <Measurement of hydrogenation rate of copolymer> The hydrogenation rate was determined by IR measurement in the same manner as the infrared spectroscopy analysis by the total reflection measurement method described above. The double bond derived from the conjugated diene monomer unit has a peak at 970 cm-1, and the hydrogenated single bond has a peak at 723 cm-1. The hydrogenation rate was calculated from the ratio of the heights of these two peaks.
[0187] <Measurement of Amide Group-Containing Structural Unit Content> The content of the amide group-containing structural unit when the amide group-containing structural unit is introduced into the copolymer through the method of hydrolyzing the nitrile group-containing structural unit was calculated by calculating the modification rate (molar ratio) of the nitrile group from the 13C-NMR quantitative spectrum by a nuclear magnetic resonance apparatus (ADVANCE400Nanobay: manufactured by Bruker Japan Co., Ltd., using CDCl3 as the measurement solvent and a 10 mm NMR tube) according to the formula [A] / ([A]+[B]), and converting it into the composition ratio (mass%) in the entire copolymer. In the table below, "Amide group amount" means "Amide group-containing structural unit content (mass%)". [A]: Peak area with chemical shift value of 180.5 to 183.5 ppm [B]: Peak area at chemical shift values of 121.5 to 123.0 ppm However, since the quantitative sensitivity of 13C-NMR measurement is low, the content of amide group-containing structural units cannot be detected unless the content is 1% or more. Therefore, for copolymers in which peaks at about 1570 cm-1 and about 1650 cm-1 derived from amide groups could be detected by IR measurement using a method similar to that of infrared spectroscopy by the total reflection measurement method described above, it was determined that the copolymer contained amide group-containing structural units, and the content of amide group-containing structural units was determined to be less than 1%. Since peaks could be detected by IR measurement similar to that described above, the content of amide group-containing structural units was determined to be 0.3% or more. In addition, when the content of amide group-containing structural units was introduced via a method of preparing a copolymer using a monomer composition containing an amide group-containing monomer, it was also determined to be less than 1% because it could not be quantified if it was less than 1%. When it was 1% or more, the ratio of the nitrile group-containing structural units and the amide group-containing structural units was confirmed by 13C-NMR quantitative spectrum, and it was confirmed that the content of the amide group-containing structural units in copolymers with a content of 1% or more of amide group-containing structural units matched the content calculated from the amount of monomer charged during synthesis.
[0188] <Measurement of the content of carboxyl group-containing structural units> The content of the carboxyl group-containing structural unit can generally be determined from the 13C-NMR quantitative spectrum using a nuclear magnetic resonance apparatus in the same manner as the measurement of the content of the amide group-containing structural unit, but when the content of the carboxyl group-containing structural unit is less than 1%, it is difficult to quantify. Therefore, in the IR measurement using the same method as the infrared spectroscopy analysis using the total reflection measurement method described above, a peak at about 1710 cm-1 due to the C=O stretching vibration was detected, and the peak at about 1570 cm-1 due to the amide group was reduced, so that it was determined that a part of the amide group was hydrolyzed to introduce a carboxyl group into the copolymer, and that the copolymer contains a carboxyl group-containing structural unit. Since a peak was detected by the IR measurement similar to that described above, it was determined that the content of the carboxyl group-containing structural unit was 0.3% or more.
[0189] <Measurement of moisture content of mixture> The water content of the mixture was measured by a Karl Fischer moisture meter (benchtop coulometric moisture meter CA-200: manufactured by Mitsubishi Chemical Analytech Corporation) by treating the sample at 230°C under a nitrogen gas flow of 250 ml / min using the Karl Fischer method, and the value was calculated as the content relative to the total mass of the copolymer, base, and solvent.
[0190] <Measurement of initial viscosity of fibrous carbon dispersion> The viscosity value was measured using a Brookfield viscometer ("BL" manufactured by Toki Sangyo Co., Ltd.) at a temperature of 25°C. After thoroughly stirring the fibrous carbon dispersion with a spatula, the viscosity value was immediately measured at a rotation speed of the Brookfield viscometer rotor of 60 rpm. The rotors used for the measurements were No. 1 when the viscosity value was less than 100 mPa·s, No. 2 when it was 100 or more and less than 500 mPa·s, No. 3 when it was 500 or more and less than 2,000 mPa·s, and No. 4 when it was 2,000 or more and less than 10,000 mPa·s. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. The obtained fibrous carbon dispersion in which there was clear separation or sedimentation was judged to have poor dispersibility. Evaluation criteria ◎: Less than 500 mPa·s (excellent) ○: 500 mPa·s or more and less than 2,000 mPa·s (good) △: 2,000 mPa·s or more and less than 10,000 mPa·s (acceptable) ×: 10,000 mPa·s or more, settling or separation (defective)
[0191] <Preparation of Copolymer 1> In a stainless steel polymerization reactor, 30 parts of acrylonitrile, 70 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.6 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Next, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through it for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solid content was dried to recover copolymer 1. The hydrogenation rate of copolymer 1 was 99.5%, and the weight average molecular weight (Mw) was 200,000. In the acrylonitrile-conjugated diene rubber, the content of the conjugated diene monomer unit was 70% and the content of the nitrile group-containing monomer unit was 30% based on the mass of the acrylonitrile-conjugated diene rubber. In addition, in copolymer 1, the content of the aliphatic hydrocarbon structural unit containing an alkylene structural unit was 70%, and the content of the nitrile group-containing monomer unit was 30% based on the mass of copolymer 1. The content of these monomer units and the content of the structural units were determined from the amount of monomer used (hereinafter the same).
[0192] <Synthesis Example 1: Preparation of Dispersant 1> In a stainless steel container 1, 16 parts of NaOH and 84 parts of NMP were placed, and the mixture was stirred with a homogenizer for 1 hour to prepare a suspension of NaOH. In a stainless steel container 2, 9 parts of copolymer 1 obtained in Synthesis Example 1 and 91 parts of NMP were placed, and the mixture was stirred with a homogenizer for 1 hour to prepare a solution of copolymer 1. Next, the suspension of NaOH and the solution of copolymer 1 were placed in a stainless steel container 3 so that NaOH and copolymer 1 had the composition shown in Table 1, and NMP was further added to adjust the concentration to obtain a mixture. The water content of the mixture was 0.1%. The mixture was stirred with a homogenizer for 2 hours to modify a part of the nitrile group of copolymer 1 to an amide group, and a dispersant 1-containing liquid (dispersant composition) containing copolymer as dispersant 1 (in the examples, the modified copolymer I may be referred to as "dispersant 1"), NMP, and NaOH was obtained. The content of the amide group-containing structural unit and the weight average molecular weight (Mw) of dispersant 1 were as shown in Table 1. In Dispersant 1, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, the content of nitrile group-containing monomer units was more than 29% and less than 30%, and the content of amide group-containing structural units was less than 1%, based on the mass of Dispersant 1. The contents of these structural units were determined using the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements (hereinafter the same).
[0193] <Preparation of Copolymer 2> Copolymer 2 was obtained in the same manner as in Synthesis Example 1, except that the monomers used were changed to 20 parts of acrylonitrile, 40 parts of 1,3-butadiene, and 40 parts of 2-methyl-1,3-butadiene. The hydrogenation rate of copolymer 2 was 99.0%, and the weight average molecular weight (Mw) was 300,000. In copolymer 2, based on the mass of copolymer 2, the content of aliphatic hydrocarbon structural units including alkylene structural units was 80%, the content of nitrile group-containing monomer units was more than 19% and less than 20%, and the content of amide group-containing structural units was less than 1%.
[0194] <Synthesis Example 2: Preparation of Dispersant 2> A dispersant 2-containing liquid was obtained in the same manner as in Synthesis Example 1, except that the copolymer used was changed to copolymer 2. The water content of the mixture of the NaOH suspension and the copolymer 2-containing liquid was 1.0%. The content and weight average molecular weight (Mw) of the amide group-containing structural unit of dispersant 2 are as shown in Table 1. In copolymer 2 (dispersant 2), the content of the aliphatic hydrocarbon structural unit containing an alkylene structural unit was 65%, the content of the nitrile group-containing monomer unit was 34.5%, and the content of the amide group-containing monomer unit was 0.5%, based on the mass of the copolymer.
[0195] The abbreviations shown in the columns for monomer and base in Table 1 and Table 2 described below have the following meanings. BD: 1,3-butadiene MBD: 2-methyl-1,3-butadiene AN: Acrylonitrile AAm: Acrylamide
[0196] <Synthesis Examples 3 and 4: Preparation of Dispersants 3 and 4> Liquids containing Dispersants 3 and 4 were obtained in the same manner as in Synthesis Example 1, except that the type and / or amount of the base used was changed according to Table 1. The content of the amide group-containing structural unit and the weight average molecular weight (Mw) of each dispersant were as shown in Table 1.
[0197] <Synthesis Example 5: Preparation of Dispersant 5> Citric acid was further added to the solution containing Dispersant 1 (copolymer 1) in an amount of 5% based on Dispersant 1 prepared in Synthesis Example 1 to modify some of the amide groups into carboxyl groups to obtain Dispersant 5. The presence of carboxyl groups was confirmed by infrared spectroscopic analysis using the total reflection measurement method. Dispersant 5 was determined to contain a carboxyl group-containing structural unit.
[0198] <Synthesis Example 6: Preparation of Dispersant 6> Into a stainless steel polymerization reactor, 34.5 parts of acrylonitrile, 65 parts of 1,3-butadiene, 0.5 parts of acrylamide, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.6 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an amide group-containing acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the mixture was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which 4 times the molar amount of nitric acid relative to palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and a hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, and the inside of the autoclave was made into a nitrogen atmosphere, after which the solid content was dried to recover dispersant 6. The hydrogenation rate of dispersant 6 was 99.5%, and the weight average molecular weight (Mw) was 200,000. In copolymer 6 (dispersant 6), the content of aliphatic hydrocarbon structural units including alkylene structural units was 65%, the content of nitrile group-containing monomer units was 34.5%, and the content of amide group-containing monomer units was 0.5%, based on the mass of copolymer 6.
[0199] FIG. 1 shows the IR spectra of copolymer 1, dispersant 1, and dispersant 3. Comparing the IR spectra of copolymer 1, dispersant 1, and dispersant 3, dispersant 3 has sharp peaks at about 1570 cm-1 and about 1650 cm-1 derived from amide groups, and dispersant 1 also has a peak derived from amide groups, although the intensity is low. On the other hand, copolymer 1 does not have an amide group, so this peak does not exist. The peak seen at about 1690 cm-1 in the vicinity is derived from the solvent NMP. From this, it was confirmed that amide groups were indeed introduced into dispersant 1 and dispersant 3. It was determined that dispersant 1 and dispersant 3 contain amide group-containing structural units. In addition, similar confirmation was performed for other dispersants.
[0200] 2 shows the 13C-NMR spectra of Dispersant 1 and Dispersant 3. The content of the amide group-containing structural unit calculated from the 13C-NMR spectrum was less than 1% for Dispersant 1 and 3.0% for Dispersant 3.
[0201] [Table 1]
[0202] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the materials and compositions shown in Table 2, a fibrous carbon dispersion was prepared as follows. First, NMP was taken in a stainless steel container and heated to 50 ° C. A dispersant was added while stirring with a disperser, and then the dispersant was dissolved by stirring for 1 hour. Next, fibrous carbon was added while stirring with a disperser, and a square hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed until the entire mixture became uniform at a speed of 8,000 rpm and the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and 50 passes of dispersion processing were performed with the high pressure homogenizer. A fibrous carbon dispersion 1 was obtained. The dispersion processing was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.
[0203] (Examples 2 to 9) Fibrous carbon dispersions 2 to 9 were obtained in the same manner as in Production Example 1, except that the materials and compositions were changed according to those shown in Table 2 and the number of passes through the high-pressure homogenizer was changed.
[0204] [Table 2]
[0205] The abbreviations used in Table 2 have the following meanings: BT1003: LUCAN BT1003M (LG Chem Ltd., multi-walled CNT, fiber diameter 13 nm) 8S: JENOTUBE8S (JEIO, multi-walled CNT, fiber diameter 6.8 nm) H-NBR1: Therban(R)3406 (LANXESS, hydrogenated acrylonitrile-butadiene rubber, acrylonitrile content 34%) PVP: Polyvinylpyrrolidone K30 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) NaOH: Sodium hydroxide (Tokyo Chemical Industry Co., Ltd., purity >98.0%, granular) KOH: Potassium hydroxide (Tokyo Chemical Industry Co., Ltd.) NMP: N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0206] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, fibrous carbon dispersion 1 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into the container of a planetary mixer (Hibismix (R) 2P-1 type, manufactured by Primix Corporation), and the mixture was stirred for 60 minutes at a rotation speed (revolution) of 60 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the obtained mixture was taken out into a stainless steel vat and vacuum-dried at 100°C for 2 hours using a vacuum dryer to completely remove the liquid components. The dried product was coarsely crushed in a mortar to obtain electrode composite for a secondary battery 1.
[0207] (Examples 1-2 to 1-8) According to the compositions shown in Table 3, Composites 2 to 8 were obtained in the same manner as in Example 1-1.
[0208] (Examples 1 to 9) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 9 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into a container of a Nobilta (NOB-MINI, manufactured by Hosokawa Micron Corporation), and the mixture was stirred for 10 minutes at a rotation speed of 5000 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 100°C for 2 hours using a vacuum dryer to completely remove the liquid component. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 9.
[0209] (Examples 1 to 10) According to the composition shown in Table 3, a composite 10 was obtained in the same manner as in Example 1-1, except that the rotation speed (revolution) of the planetary mixer was changed to 100 rpm.
[0210] (Examples 1 to 11) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 2 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into a container of Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation), and the mixture was stirred for 10 minutes at a rotation speed of 3000 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the obtained mixture was taken out into a stainless steel vat and vacuum-dried at 100°C for 2 hours using a vacuum dryer to completely remove the liquid component. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 11.
[0211] (Examples 1 to 12) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 2 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into a Trimix (TX-2L, manufactured by Inoue Seisakusho Co., Ltd.) container, and the mixture was stirred for 30 minutes at a rotation speed (revolution) of 50 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 100°C for 2 hours using a vacuum dryer to completely remove the liquid component. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 12.
[0212] (Examples 1 to 13) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into the container of a planetary mixer (Hibismix (R) 2P-1 type, manufactured by Primix Corporation), and the mixture was stirred for 60 minutes at a rotation speed (revolution) of 60 rpm to prepare a mixture. During stirring, the temperature was controlled at 25 ° C. with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 100 ° C. for 2.5 hours using a vacuum dryer to completely remove the liquid component. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 13.
[0213] (Examples 1-14) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into the container of a planetary mixer (Hibismix (R) 2P-1 type, manufactured by Primix Corporation), and the mixture was stirred for 60 minutes at a rotation speed (revolution) of 60 rpm, after which a 10% binder solution (polyvinylidene fluoride resin: KF polymer #1300) previously dissolved in NMP was added, and the mixture was stirred for 45 minutes at a rotation speed (revolution) of 60 rpm to prepare a mixture. During stirring, the temperature was controlled at 25 ° C. with a temperature-adjusting chiller. After that, the inside of the container was kept at 80 ° C. with a hot water chiller, and the mixture was dried for 3 hours under reduced pressure with a vacuum pump to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 14.
[0214] (Examples 1 to 15) According to the composition shown in Table 3, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was taken in a stainless steel container, and NMP was added while stirring with a disperser, and the mixture was stirred for 30 minutes. Next, NMC and the above dispersion were charged into the container of a high-speed mixer, and the mixture was stirred for 45 minutes at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm, after which a 10% binder solution (polyvinylidene fluoride resin: KF polymer #1300) previously dissolved in NM was added, and the mixture was stirred for 30 minutes at the same rotation speed to prepare a mixture. The temperature was controlled to 25°C with a temperature-controlled chiller during stirring. After that, the inside of the container was kept at 80°C with a hot water chiller, and the mixture was dried for 3 hours by reducing the pressure with a vacuum pump to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 15.
[0215] (Comparative Example 1-1) An electrode composite for secondary batteries was produced as follows according to the composition shown in Table 3. NMC and fibrous carbon were charged into a container of Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation) and stirred at a rotation speed of 5000 rpm for 10 minutes to obtain an electrode composite for secondary batteries 16. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller.
[0216] (Comparative Example 1-2) According to the composition shown in Table 3, NMC and fibrous carbon dispersion 2 were weighed out and placed in a container, and the mixture was stirred with a medicine spoon for 10 minutes to prepare a mixture. The mixture was then taken out into a stainless steel tray and vacuum dried at 100°C for 2 hours using a vacuum dryer to completely remove the liquid components. The dried product was coarsely crushed in a mortar to obtain electrode composite 17 for secondary batteries.
[0217] (Comparative Examples 1-3 and 1-4) Composites 18 and 19 were obtained in the same manner as in Example 1-1, except that the drying temperature and drying time were changed to 120° C. and 4 hours, according to the compositions shown in Table 3.
[0218] <Evaluation of the state of fibrous carbon in composites> The dispersion state of the fibrous carbon in the composite was determined using a JEOL JSM-7800F scanning electron microscope. · Criteria for determining aggregates of fibrous carbon ◎: Contains or does not contain fibrous carbon aggregates of 5 μm or less. ○: Contains aggregates of fibrous carbon larger than 5 μm and smaller than 10 μm. △: Contains aggregates of fibrous carbon larger than 10 μm and smaller than 50 μm ×: Contains aggregates of fibrous carbon larger than 50 μm Criteria for determining the surface disintegration state of fibrous carbon active material ◎: The area of fibrous carbon adsorbed on the active material in a crushed fiber state is 50% or more of the entire surface area of the active material. ○: The area of the fibrous carbon adsorbed on the active material in a crushed state is 20% or more and less than 50% of the entire surface of the active material. △: The area of the fibrous carbon adsorbed on the active material in a crushed state is 10% or more and less than 20% of the entire surface area of the active material. ×: The fibers are not adsorbed to the active material in a crushed state.
[0219] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance ThermoplusEV02TG8121 manufactured by Rigaku. The exothermic peak temperature obtained when the temperature was increased from 40°C to 800°C at 10°C / min while flowing compressed air at 200mL / min was used as an index. The exothermic peak temperature was calculated by reading the peak top temperature of the exothermic peak due to the combustion of the fibrous carbon in the range of 400 to 700°C in the DTA curve obtained by measurement.
[0220] [Table 3]
[0221] The abbreviations used in Table 3 have the following meanings: ·NMC: NCM523 (manufactured by Nihon Kagaku Kogyo Co., Ltd., composition: LiNi 0.5 Co 0.2 Mn 0.3 O2)
[0222] As shown in Table 3, from the SEM and TG-DTA exothermic peak temperatures, it can be seen that in the Examples, the fibrous carbon in the composite was in a state of being appropriately disintegrated and adsorbed on the active material surface without excessive aggregation. On the other hand, in the Comparative Examples, the disintegration of the aggregates of the fibrous carbon and the adsorption of the disintegrated material on the active material surface were insufficient.
[0223] <Preparation of the positive electrode film> A positive electrode film was produced using the electrode composite produced in the example. 1.5 parts of polyvinylidene fluoride resin (KF polymer #1300) as a binder and 98.5 parts of electrode composite 1 were weighed out and placed in a plastic container, and stirred for 15 seconds at 2,000 rpm using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). The resulting powder mixture was calendered onto an aluminum foil current collector with a thickness of 20 μm using a powder feeder and a calender roll (roll temperature 200°C), to obtain electrode film 1 for the positive electrode. The density of the electrode film for the positive electrode was 3.0 g / cm. 3 It was.
[0224] Positive electrode films 2 to 13 and 16 to 19 were obtained in the same manner as in the positive electrode film 1 using the composites 2 to 13 and 16 to 19.
[0225] 0.75 parts of polyvinylidene fluoride resin (KF polymer #1300) as a binder and 99.25 parts of electrode composite 14 were weighed out and placed in a plastic container, and stirred at 2,000 rpm for 15 seconds using a centrifugal mixer (Thinky's Awatori Rentaro, ARE-310). The resulting powder mixture was calendered onto an aluminum foil current collector with a thickness of 20 μm using a powder feeder and a calender roll (roll temperature 200°C), to obtain an electrode film for the positive electrode 14. The density of the electrode film for the positive electrode was 3.0 g / cm. 3 It was.
[0226] The composite 15 was used to obtain a positive electrode film 15 in the same manner as the positive electrode film 14 .
[0227] (Resistance of the positive electrode film) The volume resistivity of the electrode films 1 to 19 was measured by a four-probe method using Loresta GP (manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS-K7194. For the resistance measurement, a measurement electrode was used in which the coating substrate used in the preparation of each electrode was changed from aluminum foil to a PET substrate. A relative value (%) was determined based on the volume resistivity of the electrode film of Comparative Example 1-3, and evaluated according to the following criteria. Criteria for electrode resistance characteristics ◎: Over 200% (Excellent) ○: 150% or more but less than 200% (Excellent) ○△: 100% or more but less than 150% (good) △: 50% or more but less than 100% (defective) ×: Less than 50% (extremely poor)
[0228] <Assembly of a cell for evaluating the positive electrode of a lithium-ion secondary battery> The previously prepared electrode films 1 to 19 were punched out to φ16 mm to be used as the working electrode, and a metallic lithium foil (thickness 0.15 mm) was used as the counter electrode. A separator (porous polypropylene film) was inserted and laminated between the working electrode and the counter electrode, and a bipolar sealed metal cell (Hosen HS Flat Cell) was assembled by filling it with an electrolyte (a non-aqueous electrolyte in which LiPF6 was dissolved at a concentration of 1M in a mixed solvent in which ethylene carbonate and diethyl carbonate were mixed at a volume ratio of 1:1). The cell was assembled in a glove box substituted with argon gas.
[0229] <Evaluation of rate characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C and a discharge end voltage of 2.5V. This operation was repeated three times, and then constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, and constant current discharging was performed at a discharge rate of 3C and a discharge end voltage of 2.5V. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 0.2C discharge capacity x 100 (%) The relative value (%) was calculated based on the rate characteristic of Comparative Example 1-3, and evaluated according to the following criteria. Rate characteristic criteria ◎: 150% or more (very good) ○: 130% or more but less than 150% (Excellent) ○△: 100% or more but less than 130% (good) ×: Less than 100% (defective)
[0230] <Evaluation of cycle characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C with a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 60th 0.2C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 3rd 0.2C discharge capacity / 60th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristics of Comparative Example 1-3, and the results were evaluated according to the following criteria. Cycle performance criteria ◎: 180% or more (excellent) ○: 150% or more but less than 180% (Excellent) ○△: 100% or more but less than 150% (good) ×: Less than 100% (defective) [Table 4]
[0231] As shown in Table 4, the examples showed superior battery characteristics compared to the comparative examples. The fibrous carbon in the composite of the examples was not excessively aggregated, but was loosened and adsorbed on the surface of the active material. It is presumed that this allowed the conductive path in the electrode to be formed uniformly, leading to reduced electrode resistance and improved rate characteristics and cycle characteristics. Among them, those in which the fibrous carbon was well adsorbed showed particularly good performance. On the other hand, in the comparative example, insufficient crushing of the fibrous carbon during the composite manufacturing process and excessive drying and aggregation during the drying process resulted in a decrease in the amount of adsorption onto the active material surface and uneven distribution of the material, which is presumably responsible for the uneven formation of conductive paths within the electrode, leading to an increase in electrode resistance and deterioration of rate characteristics and cycle characteristics. From the above, it was demonstrated that the electrode composite produced by the production method of the present invention can exhibit excellent battery characteristics.
Claims
1. A method for producing a composite for a secondary battery electrode, comprising: A method for producing a composite for a secondary battery electrode, comprising the steps of: combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer; and removing the solvent and drying the resulting mixture.
2. The fibrous carbon dispersion includes fibrous carbon, a dispersant, and a solvent, 2. The method for producing a composite for a secondary battery electrode in accordance with claim 1, wherein the dispersant comprises a copolymer containing an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit.
3. The copolymer is The copolymer contains an aliphatic hydrocarbon structural unit, a nitrile group-containing structural unit, and an alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit, the aliphatic hydrocarbon structural unit contains an alkylene structural unit, the content of the aliphatic hydrocarbon structural unit is 40% by mass or more and less than 85% by mass based on the mass of the copolymer, the content of the nitrile group-containing structural unit is 15% by mass or more and 50% by mass or less based on the mass of the copolymer, and the content of the alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit is 10% by mass or less based on the mass of the copolymer, a total content of the aliphatic hydrocarbon structural unit, the nitrile group-containing structural unit, and the alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit is 80 mass% or more based on the mass of the copolymer, 3. The method for producing a composite for a secondary battery electrode in accordance with claim 2, wherein the weight average molecular weight of said copolymer is from 5,000 to 400,000.
4. The method for producing a composite for a secondary battery electrode according to claim 2 or 3, wherein the copolymer further contains less than 1 mass % of a carboxyl group-containing structural unit based on the mass of the copolymer.
5. 4. The method for producing a composite for a secondary battery electrode according to claim 2, wherein the fibrous carbon dispersion contains 1 mass % or more and 20 mass % or less of a base based on the mass of the copolymer.
6. 3. The method for producing a composite for a secondary battery electrode according to claim 1 or 2, characterized in that the composite for a secondary battery electrode has an exothermic peak temperature of 520° C. or less of the fibrous carbon obtained by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere.
7. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the composite for a secondary battery electrode contains a binder resin.
8. A method for producing an electrode film, comprising: preparing an electrode composite for a secondary battery according to the method according to claim 1 or 2; and forming an electrode film using the electrode composite for a secondary battery.
9. A method for producing a secondary battery, comprising: preparing an electrode composite for a secondary battery according to the method according to claim 1 or 2; and forming an electrode film using the electrode composite for a secondary battery.
Citation Information
Patent Citations
Electrode for secondary battery and secondary battery using this
JP2004186075A
Lithium titanate crystal structure, complex of lithium titanate crystal structure and carbon, manufacturing method for the same, electrode and electrochemical element using same
JP2011236061A
Composite of metal oxide and carbon nanotube, production method of the same, and electrode and electrochemical element using the same
JP2013075809A
Lithium nickelate-carbon composite positive electrode active material particle powder, and manufacturing method thereof, and nonaqueous electrolyte secondary battery
JP2017142997A
Carbon nanotube dispersion and use thereof
JP2020029471A